Recent Advances in Nano-Enabled Seed Treatment Strategies for Sustainable Agriculture: Challenges, Risk Assessment, and Future Perspectives - Shelar, Amruta; Nile, Shivraj Hariram; Singh, Ajay Vikram; Rothenstein, Dirk; Bill, Joachim; Xiao, Jianbo; Chaskar, Manohar; Kai, Guoyin; Patil, Rajendra (Nano-Micro Letters, 2023)
Agro seeds are vulnerable to environmental stressors, adversely affecting seed vigor, crop growth, and crop productivity. Different agrochemical-based seed treatments enhance seed germination, but they can also cause damage to the environment; therefore, sustainable technologies such as nano-based agrochemicals are urgently needed. Nanoagrochemicals can reduce the dose-dependent toxicity of seed treatment, thereby improving seed viability and ensuring the controlled release of nanoagrochemical active ingredients However, the applications of nanoagrochemicals to plants in the field raise concerns about nanomaterial safety, exposure levels, and toxicological implications to the environment and human health. In the present comprehensive review, the development, scope, challenges, and risk assessments of nanoagrochemicals on seed treatment are discussed. Moreover, the implementation obstacles for nanoagrochemicals use in seed treatments, their commercialization potential, and the need for policy regulations to assess possible risks are also discussed. Based on our knowledge, this is the first time that we have presented legendary literature to readers in order to help them gain a deeper understanding of upcoming nanotechnologies that may enable the development of future generation seed treatment agrochemical formulations, their scope, and potential risks associated with seed treatment. Highlights: 1 Novel insights on recent advances in nanotechnology-based agro seed treatment formulations. 2 Details on reducing the environmental impact of seed treatment by using nanoagrochemicals. 3 Applications of potential of nanopesticides and nanofertilizers for sustainable seed treatments. 4 Described scope of possible next-generation nanomaterials for seed treatment formulations with associated challenges and risks assessment methodologies.